Role of N-Nitro-L-Arginine-Methylester in Neuroprotection of Cerebral Ischemic Preconditioning in Rats - Awooda, Hiba A. (Asian Journal of Pharmaceutics (AJP), 2020)
Background and Aim: Ischemic preconditioning (IPC) is a phenomenon in which brief episodes of ischemia protect the brain from subsequent, severe ischemic insult. This study evaluated whether the neuroprotective effect of cerebral IPC is mediated by nitric oxide synthase (NOS) inhibition, using non-selective NOS inhibitor, and N-Nitro- L-Arginine-Methylester (L-NAME). Materials and Methods: Fifty adult male Wistar rats divided into five groups ten in each: (1) Sham-operated group (control), (2) ischemia-reperfusion (I/R) group; rats subjected to 30 min of left common carotid artery (CCA) occlusion followed by 24-h of reperfusion, (3) I/R with NOS inhibition group; rats infused with L-NAME intraperitoneally 15 min before the same I/R period, (4) IPC group; rats treated with three 5-min episodes of CCA occlusion (CCAO) with 10 min of reperfusion between stimuli, then 30 min of CCAO followed by 24 h reperfusion, and (5) IPC with NOS inhibition group: Rats were subjected to the same preconditioning stimuli as Group 4 with the infusion of NOS inhibitor (L-NAME) 15 mg/kg, 15 min before CCAO. Neurological assessments were evaluated, enzyme-linked immunosorbent assay used to detect Rho-kinases (ROCK), and nitric oxide metabolites were measured colorimetrically. Results: IPC significantly reduces the neurological deficit and lowering the ROCK level with higher nitrite levels. While administration of L-NAME in IPC rats results in a significant enhancement in neurological scoring compared to IPC without NOS inhibition, with significant inhibition of nitrite and ROCK. Conclusion: Despite previous evidence that NO involves in neuroprotective mechanism of IPC, the current data suggest the potential ofL-NAME as a neuroprotective component of IPC.